Dual-stage continuous-flow seedless microfluidic synthesis of anisotropic gold nanocrystals - Duraiswamy, Suhanya (2014)
Continuous-flow multi-step synthesis of anisotropic gold nanocrystals is demonstrated, in which gold nanoparticle seed synthesis and subsequent growth is accomplished in a two-stage droplet-based microfluidic device. The method successfully integrates synthesis of gold nanoparticle seeds and their further growth into spheres, rods, dog-bone shaped, and sharp-edged nanostructures with signature plasmon resonances.